European Convention on Human Rights from the perspective of the Republic of Serbia - Plavsic, Natasa (European Integration Studies, 2025)
This article explores the role of the European Convention on Human Rights (ECHR) in the constitutional and legal order of the Republic of Serbia. It outlines the historical development of the constitutional guarantees of human rights and the gradual incorporation of international human rights standards into domestic constitutional law. The paper discusses the constitutional stratus of the ECHR and the obligation of the domestic authorities to interpret national law in accordance with the case-law of the European Court of Human Rights. Particular focus is placed on the role of the Constitutional Court as a key domestic mechanism for the protection of Convention rights. The paper analyses selected landmark cases against Serbia and highlights the transformative effect of the ECtHR jurisprudence on national law and judicial practice. The paper concludes that effective implementation of the Convention remains essential for ensuring sustainable human rights protection in Serbia.